Platinum-catalyzed hydrolysis etching of SiC in water: A density functional theory study. (17th April 2018) - Van Bui, Pho; Toh, Daisetsu; Isohashi, Ai; Matsuyama, Satoshi; Inagaki, Kouji; Sano, Yasuhisa; Yamauchi, Kazuto; Morikawa, Yoshitada
Abstract: A comprehensive study of the physicochemical interactions and the reaction mechanism of SiC etching with water by Pt catalysts can reveal key details about the surface treatment and catalytic phenomena at interfaces. Therefore, density functional theory simulations were performed to study the kinetics of Pt-assisted water dissociation and breaking of a Si–C bond compared to the HF-assisted mechanism. These calculations carefully considered the elastic and chemical interaction energies at the Pt–SiC interface, activation barriers of Si–C bond dissociation, and the catalytic role of Pt. It was found that the Pt-catalyzed etching of SiC in water is initiated via hydrolysis reactions that break the topmost Si–C bonds. The activation barrier strongly depends on the elastic and chemical interactions. However, chemical interactions are a dominant factor and mainly contribute to the lowering of the activation barrier, resulting in an increased rate of reaction.